Influence of Strength, Power, and Muscular Stiffness on Stroke Velocity in Junior Tennis Players - Colomar, Joshua; Baiget, Ernest; Corbi, Francisco (Frontiers in Physiology, 2020)
Objective: The main aim of this study was to establish the relationship between strength, power characteristics, individual muscle stiffness, International Tennis Number (ITN) and stroke velocity (StV) in junior tennis players and to determine a prediction model based on the relationship between these variables. Methods: 21 junior male tennis players (mean ± SD; age, 17.0 ± 0.8 years; height, 1.8 ± 0.1 m; body mass, 72.3 ± 5.8 kg; BMI 22.1 ± 1.5 kg/m2), with an ITN ranging from 2 to 4, performed measurements regarding muscle stiffness of selected muscles involved in tennis strokes. StV (serve, forehand and backhand), strength (maximum isometric strength) and power (medicine ball throws, squat jump, countermovement jump and bench press) measurements were also performed (ICC = 0.803-0.998; CV = 0.3-6.4). Results: Moderate inverse correlations were found between serve velocity (SV) and ITN (r = -0.43; p = 0.05), and large positive correlations were observed between pectoralis majoris stiffness (PMStiff) (r = 0.53; p = 0.01), isometric wrist flexion (r = 0.58; p = 0.006) and ITN respectively. PMStiff was moderately inversely correlated to forehand velocity (FV) (r = -0.45; p = 0.03) and gastrocnemius (GStiff) and infraspinatus stiffness (IStiff) positively to SV (r = 0.45; p = 0.04; r = 0.42; p = 0.05). No significant correlations were found regarding strength and power measurements. ITN, IStiff and PMStiff explained 34% and 21% of variability in SV and FV respectively. Conclusion: Greater stiffness values may enhance StV, especially when transferring power from lower to upper body. On the other hand, high scores could interfere in technical parameters that are key for velocity production in complex tennis strokes. Strength and power values proved to correlate poorly to StV in this particular sample of junior tennis players, possibly due to the multifactorial nature of tennis strokes and the possibility that they become more important as age and level increase.